2023
DOI: 10.1021/acs.molpharmaceut.3c00334
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model for Cocrystal Dissolution with Simultaneous Surface and Bulk Precipitation

Nethrue Pramuditha Mendis,
Richard Lakerveld

Abstract: Cocrystals can be promising means of overcoming the poor aqueous solubility of many drugs. However, precipitation of the stable drug at the cocrystal surface or in the bulk medium is often provoked during cocrystal dissolution due to high drug supersaturation, which prevents sustaining high drug concentrations for enhanced bioavailability. There is a need for predictive in vitro models that can accurately describe this cocrystal dissolution−supersaturation−precipitation (DSP) process to aid drug development an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…135 The difference between the bulk and interfacial pH microenvironment generated by mass transfer limitations, together with the promotion of heterogeneous nucleation on the cocrystal surface, accounts for the presence of PS-SMPT. 136,137 Xuan and co-worker elucidated the phase transformation behavior of various curcumin cocrystals during dissolution at the molecular level. The solution-state stability of curcumin cocrystals was found to be affected by both the composition of dissolution medium and the cocrystal intrinsic thermodynamic stability.…”
Section: Merits and Perilsmentioning
confidence: 99%
See 1 more Smart Citation
“…135 The difference between the bulk and interfacial pH microenvironment generated by mass transfer limitations, together with the promotion of heterogeneous nucleation on the cocrystal surface, accounts for the presence of PS-SMPT. 136,137 Xuan and co-worker elucidated the phase transformation behavior of various curcumin cocrystals during dissolution at the molecular level. The solution-state stability of curcumin cocrystals was found to be affected by both the composition of dissolution medium and the cocrystal intrinsic thermodynamic stability.…”
Section: Merits and Perilsmentioning
confidence: 99%
“…The dissolution–supersaturation–precipitation (DSP) profile is also intriguingly shaped by the cocrystal concentration. Mendis and Lakerveld have recently developed a predictive dynamic model for the concentration-dependent DSP behavior of dissolving cocrystals in vitro when considering both surface and bulk precipitation, 136 which showed that the cocrystal concentration should only be moderately high to sustain a high supersaturation. For instance, five concentrations (15, 20, 30, 40, and 50 mg in 50 mL of the dissolution medium) of the carbamazepine–succinic acid cocrystal were tested in dissolution experiments.…”
Section: Merits and Perilsmentioning
confidence: 99%